Unified efficiency evaluation of regional industries in China: a nonradial directional distance function approach. Issue 16 (20th September 2017) - Liang, Jun; Long, Shaobo
ABSTRACT: This article extends a nonradial directional distance function (DDF) to allow decision-making units to adjust inputs in two directions. Based on this nonradial DDF, we evaluate the regional industrial unified efficiency (operational efficiency and environmental efficiency) in China between 2005 and 2014. We find that East China has the highest industrial unified efficiency score, followed by the West and Central China. To avoid methodological biases, three other models are also applied to assess the unified efficiency. The results indicate that a nonradial DDF under natural and managerial disposability (our model) has a greater discriminating power than a nonradial DDF under either of the disposabilities and the radial DDF.